Принцип доцільності в кримінально-правовій доктрині та кримінальному законодавстві України - Степаненко, Оксана Василівна; Степаненко, Оксана Васильевна; Stepanenko, Oksana V. (My University, 2017)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.08 - кримінальне право та кримінологія; кримінально- виконавче право. - Національний університет «Одеська юридична академія», Одеса, 2017. Дисертація є першим у вітчизняній науці кримінального права спеціальним комплексним дослідженням методологічних, теоретичних та практичних аспектів принципу доцільності в кримінально-правовій доктрині та кримінальному законодавстві України. У дисертації сформульовано методологічні засади дослідження принципу доцільності в кримінально-правовій доктрині та кримінальному законодавстві України. Сформульовано поняття категорії «доцільність» в кримінальному праві та виокремлено її характерні ознаки. Визначено поняття, зміст та ознаки принципу доцільності в кримінальному праві. Досліджено генезис принципу доцільності в кримінально-правовій доктрині та кримінальному законодавстві України. Розглянуто місце і роль принципу доцільності в системі принципів кримінального права. З'ясовано проблеми реалізації принципу доцільності при здійсненні кримінально-правового регулювання та запропоновано шляхи їх вирішення. Сформульовано науково-обґрунтовані пропозиції про внесення змін та доповнень до кримінального законодавства України щодо реалізації принципу доцільності.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.08 - уголовное право и криминология; уголовно-исполнительное право. - Национальный университет «Одесская юридическая академия», Одесса, 2017. Диссертация является первым в отечественной науке уголовного права специальным комплексным исследованием методологических, теоретических и практических аспектов принципа целесообразности в уголовно-правовой доктрине и уголовном законодательстве Украины. В диссертации сформулированы методологические основы исследования принципа целесообразности в уголовно-правовой доктрине и уголовном законодательстве Украины. Сформулировано понятие категории «целесообразность» в уголовном праве и выделено ее характерные признаки. Определено понятие, содержание и признаки принципа целесообразности в уголовном праве. Исследован генезис принципа целесообразности в уголовно-правовой доктрине и уголовном законодательстве Украины. Рассмотрено место и роль принципа целесообразности в системе принципов уголовного права. Установлены проблемы реализации принципа целесообразности при осуществлении уголовно-правового регулирования и предложено пути их решения. Сформулированы научно-обоснованные предложения о внесении изменений и дополнений в уголовное законодательство Украины в сфере реализации принципа целесообразности.

Thesis for obtaining scientific degree of Candidate of Juridical Science, specialty 12.00.08 - criminal law and criminology; penal law. - National University «Odessa Law Academy», Odessa, 2017. The thesis is the first in Ukraine special complex research of theoretical, methodological and practical aspects of expediency principle in criminal law doctrine and criminal legislation of Ukraine. Methodological principles of researching expediency principle in criminal law were formulated in the thesis; the concept of expediency principle of criminal law is suggested; the importance of expediency principle in criminal law doctrine of Ukraine was ascertained as well. The genesis of expediency principle in criminal law of Ukraine is explored and subsequent stages of its formation were defined. It is established that «expediency» has all indispensable characteristics to be a principle of criminal law (objectively-subjective character; regulatory; reflection of content of the General and Special parts of the Criminal Code of Ukraine (universality); obligatoriness on two levels of criminal law regulation: lawmaking and law-enforcing (general significance); systemacy that allows considering the expediency as one of the principles of criminal law. It is suggested to define principle in criminal law as a guiding idea that reflects content of law of criminal liability and stipulates exercising of lawmaking and lawenforcing activity to attain the goals and objectives of criminal law taking into account specific circumstances and tendency of development of criminal law. It is justified that principles of criminal law constitute a system that is characterized by equality of all elements. The place of the expediency principle among other principles of criminal law was determined and it is stated that the expediency principle is not isolated from other principles of criminal law but exists in unity and interrelation with them. Considering that the expediency principle in criminal law defines the effectiveness of criminal law regulation the content and importance of the expediency principle during enforcement of criminal law (qualification of criminal offences, discharge from criminal liability and imposition of punishment) as well as in the sphere of criminal lawmaking is defined. On the basis of thorough research of the criminal law, its doctrine and enforcement practice theoretically justified proposals and changes to the Criminal Code of Ukraine in the sphere of enforcement of the expediency principle in criminal law are formulated.
дис. ... к.ю.н.: 12.00.08
Степаненко О.В. Принцип доцільності в кримінально-правовій доктрині та кримінальному законодавстві України: дис. ... канд. юрид. наук: 12.00.08 / Степаненко Оксана Василівна. - Одесса, 2017. - 249 с.
Keywords: цілі кримінального права; завдання кримінального права; доцільність; принципи кримінального права; принцип доцільності; цели уголовного права; задачи уголовного права; целесообразность; принципы уголовного права; принцип целесообразности; goals of criminal law; objectives of criminal law; expediency; principles of criminal law; expediency principle